Peta Religiositas berdasarkan Islamic Worldview pada Milenial Muslim di Yogyakarta - Anita Anita; Badrun Kartowagiran; Ayub Ayub (Universitas Darussalam Gontor, 2019)
AbstractIslamic civilization is built upon Islam as a distinctive religion and way of life (dîn). Therefore, the fate of this civilization depends on the religiosity of each Muslim individuals. In this context, an empirical study to map Muslim religiosity becomes necessary. However, studies of Muslim religiosity have been imbued with conceptual as well as epistemological bias due to the adaptation of instruments that were developed based on the Judeo-Christian traditions. This article presents a mapping of Muslim millennial religiosity (306 respondents) using The Muslim Religiosity-Personality Inventory (MRPI), an instrument developed based on the concept of Islamic Worldview. Muslim millennials were chosen because of their strategic demographic position in the development of Islamic civilization. The religiosity of the respondents would be analyzed by referring to two dimensions of Islamic religiosity, namely Islamic Worldview and Religious Personality. Regarding the first dimension, this research revealed that millennials Muslims in Yogyakarta strongly believe in God's active involvement in the affairs of His creatures. However, they lack the understanding of the nature of the involvement. They also have a low score in some crucial aspects of Islamic worldview such as the universality of Islamic teachings and the concept of fithrah (human nature). Regarding the second dimension, they have a high score on personal religiosity, medium score on social religiosity (mu’âmalât), and a low score in ritual religiosity (‘ibâdah mahdhah). This article will further discuss the implications of the findings to the development of Islamic civilization. Keywords: Religiosity, Millennial Muslim, Islamic Worldview, Religious Personality. AbstrakPeradaban Islam dibangun di atas fondasi Islam sebagai agama (dîn) yang distingtif dan unggul. Oleh karena itu, nasib peradaban ini tergantung kepada sejauh mana tiap Muslim menghayati agamanya. Dalam konteks ini, kajian religiositas yang empiris untuk memetakan keberagamaan ini menjadi perlu. Namun, selama ini kajian religiositas masih bias secara konseptual dan epistemologis, sebab kebanyakan instrumen yang digunakan berasal dari tradisi Yahudi atau Kristen. Artikel ini menyajikan pemetaan religiositas milenial Muslim (sampel 306 orang) dengan menggunakan The Muslim Religiosity-Personality Inventory (MRPI), sebuah instrumen yang dikembangkan berasaskan konsep Islamic Worldview. Milenial Muslim dipilih sebab posisi demografis mereka yang strategis dalam pembangunan peradaban. Data religiositas responden dipetakan dengan dengan merujuk kepada dua dimensi yaitu Islamic Worldview (IW) dan Religious Personality (RP). Dari dimensi IW, ditemukan bahwa milenial Muslim di Yogyakarta meyakini keterlibatan mutlak Allah di alam, tapi belum memahami dengan baik mekanisme hubungan Allah dengan ciptaan-Nya. Mereka juga memperoleh skor rendah dalam aspek krusial seperti tentang keuniversalan ajaran Islam dan pandangan tentang fitrah manusia. Pada dimensi RP milenial Muslim memiliki skor kesalehan personal yang tinggi disusul kesalehan sosial (mu’âmalât). Namun skor mereka rendah dalam ranah ritual (‘ibâdah mahdhah). Artikel ini juga akan mendiskusikan signifikansi skor yang diperoleh responden pada tiap indikator di atas terhadap upaya pembangunan peradaban Islam.Kata Kunci: Religiositas, Milenial Muslim, Worldview Islam, Kepribadian Religius.